Once-Weekly Dulaglutide for the Treatment of Youths with Type 2 Diabetes - Arslanian, Silva A.; Hannon, Tamara; Zeitler, Philip; Chao, Lily C.; Boucher-Berry, Claudia; Barrientos-Pérez, Margarita; Bismuth, Elise; Dib, Sergio; Cho, Jang Ik; Cox, David (The New England journal of medicine, 2022)
This trial compared once-weekly dulaglutide, a GLP-1 receptor agonist, with placebo for glycemic control in youths with type 2 diabetes who may have been receiving metformin or basal insulin. Dulaglutide was superior at 26 weeks.